Students' Comprehension about the Concept of Light through Generative Learning Model - Rosdianto, Haris (Jurnal Pendidikan Indonesia, 2017)
This study aims to determine the effect of generative learning model on the students’ conceptual understanding on Lights subject matter. This type of research is pre experimental study with One Group Pretest Posttest Design. The population of this research is all students of class VIII in SMP 5 Singkawang city. The sample of the research is the students of class VIII E which amounted to 20 people and the sampling technique using simple random sampling. The research instrument used in the form of multiple choice test. Data were analyzed by using paired t-test. From the calculation results obtained value -tcalculation < -ttable ie -59,73 < -2,093, then H0 rejected and Ha accepted at the level of significance α = 0,05. So it can be concluded that there is influence of generative learning model to students’ concept understanding on lights subject matter.